2021
DOI: 10.1093/rap/rkab088
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the nail and systemic enthesitis in psoriatic arthritis

Abstract: Objective Psoriatic nail disease is more common in PsA than in isolated skin psoriasis (PsO). The nail is closely integrated to the DIP joint entheses. US data have shown that those patients with nail disease in PsO are more likely to have systemic enthesitis. We examined whether there was a relationship between nail disease, DIP enthesitis and systemic enthesitis in established PsA. Methods Forty-six PsA participants with na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Furthermore, this subclinical nail involvement could reinforce the concept of psoriatic disease continuum, ranging from skin involvement to the musculoskeletal manifestations [ 34 ]. According to the nail-entheseal pathogenesis proposed in psoriatic disease [ 1 , 9 , 35 ], the nail lesions are frequently associated with the presence of enthesis involvement suggesting the relevance of their evaluation in managing these patients [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this subclinical nail involvement could reinforce the concept of psoriatic disease continuum, ranging from skin involvement to the musculoskeletal manifestations [ 34 ]. According to the nail-entheseal pathogenesis proposed in psoriatic disease [ 1 , 9 , 35 ], the nail lesions are frequently associated with the presence of enthesis involvement suggesting the relevance of their evaluation in managing these patients [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is to our knowledge the first paper that has assessed a change in ultrasound-confirmed enthesitis in PsA between different classes of biologic therapies. 17 Ultimately, we have seen an overall decrease in ultrasound confirmed entheseal disease for both classes of biologic therapy. In terms of comparing ultrasound response for the treatments administered, there was a larger Other studies have demonstrated a weak correlation between the MASEI and the clinical LEI scores 18 but interestingly that research group when only assessing the clinical sites of the MASEI did not see a correlation with ultrasound MASEI scores.…”
Section: Discussionmentioning
confidence: 76%